Impacts of licensed premises trading hour policies on alcohol‐related harms. (2nd March 2018) - Atkinson, Jo‐An; Prodan, Ante; Livingston, Michael; Knowles, Dylan; O'Donnell, Eloise; Room, Robin; Indig, Devon; Page, Andrew; McDonnell, Geoff; Wiggers, John
Abstract: Background and aim: Evaluations of alcohol policy changes demonstrate that restriction of trading hours of both 'on'‐ and 'off'‐licence venues can be an effective means of reducing rates of alcohol‐related harm. Despite this, the effects of different trading hour policy options over time, accounting for different contexts and demographic characteristics, and the common co‐occurrence of other harm reduction strategies in trading hour policy initiatives, are difficult to estimate. The aim of this study was to use dynamic simulation modelling to compare estimated impacts over time of a range of trading hour policy options on various indicators of acute alcohol‐related harm. Methods: An agent‐based model of alcohol consumption in New South Wales, Australia was developed using existing research evidence, analysis of available data and a structured approach to incorporating expert opinion. Five policy scenarios were simulated, including restrictions to trading hours of on‐licence venues and extensions to trading hours of bottle shops. The impact of the scenarios on four measures of alcohol‐related harm were considered: total acute harms, alcohol‐related violence, emergency department (ED) presentations and hospitalizations. Results: Simulation of a 3 a.m. (rather than 5 a.m.) closing time resulted in an estimated 12.3 ± 2.4% reduction in total acute alcohol‐related harms, a 7.9 ± 0.8% reduction in violence, an 11.9 ± 2.1% reduction in ED presentations and a 9.5 ± 1.8% reduction in hospitalizations. Further reductions were achieved simulating a 1 a.m. closing time, including a 17.5 ± 1.1% reduction in alcohol‐related violence. Simulated extensions to bottle shop trading hours resulted in increases in rates of all four measures of harm, although most of the effects came from increasing operating hours from 10 p.m. to 11 p.m. Conclusions: An agent‐based simulation model suggests that restricting trading hours of licensed venues reduces rates of alcohol‐related harm and extending trading hours of bottle shops increases rates of alcohol‐related harm. The model can estimate the effects of a range of policy options.